Managing Waldenström's macroglobulinemia with BTK inhibitors - Buske, Christian; Jurczak, Wojciech; Salem, Joe-Elie; Dimopoulos, Meletios A (Leukemia, 2023)
Bruton's tyrosine kinase (BTK) inhibition is one of the treatment standards for patients with relapsed/refractory Waldenström's macroglobulinemia (WM) and for patients with WM who are unsuitable for immunochemotherapy (ICT). It offers deep and durable responses with a manageable safety profile that is generally favorable compared with ICT regimens. However, the limitations of the first approved BTK inhibitor (BTKi), ibrutinib, include reduced efficacy in patients lacking the characteristic WM mutation (MYD88 ) and toxicities related to off-target activity. The risk of atrial fibrillation (AF) and other cardiovascular side effects are a notable feature of ibrutinib therapy. Several next-generation covalent BTKis with greater selectivity for BTK are at various stages of development. In November 2021, zanubrutinib became the first of these agents to be approved by the European Medicines Agency for the treatment of WM. Head-to-head trial data indicate that it has comparable efficacy to ibrutinib for patients with WM overall, although it may be more effective in patients with CXCR4 mutations or wild-type MYD88. In the clinical trial setting, its greater selectivity translates into a reduced risk of cardiovascular side effects, including AF. Acalabrutinib, which is pre-approval in WM, appears to offer similar advantages over ibrutinib in terms of its safety profile. Beyond the next-generation covalent BTKis, non-covalent BTKis are an emerging class with the potential to provide a therapeutic option for patients who relapse on covalent BTKis. In the future, BTKis may be increasingly utilized within combination regimens. Several ongoing trials in WM are investigating the potential for BTKi use in combination with established and novel targeted agents.